comics, reading interest, Arabic IMPLEMENTASI MEDIA BUKU CERITA BERGAMBAR (KOMIK) UNTUK MENINGKATKAN MINAT BACA BAHASA ARAB SANTRI PONDOK PESANTREN MAHASISWA SIROJUT THOLIBIN TULUNGAGUNG - Frisna Septian Renaldi; Nazhifatul Ulfah (Jurnal Studi Pesantren, 2025)
This study aims to implement illustrated storybooks (comics) as a learning medium to enhance reading interest and Arabic language skills (maharah qiraah) among students at Pondok Pesantren Sirojut Tholibin Tulungagung. This research uses a qualitative approach. Data was obtained through interviews, observation and documentation. The findings revealed that Arabic-language comics significantly improved the students' reading skills, created an enjoyable learning environment, and fostered interest in Arabic literature. Comics as a learning medium proved to be relevant to the students' interests and made the learning process more effective, interactive, and meaningful. These findings underscore the importance of innovation in teaching methods to address challenges in Arabic language learning among students.